Unveiling Gen Z Muslim Purchase Decisions: The Role of Product Quality, Social Media, and Halal Labeling in Indonesia’s Instant Noodle Market - Ifran Nabhani (International Journal of Science and Environment (IJSE), 2025)
This research examines the factors influencing the purchasing decisions of instant noodles among Generation Z (Gen Z) Muslims in Indonesia, focusing on product quality, halal labels, social media, and trust in the product. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) and data from 210 respondents, this study aims to understand the relationships among these variables and the role of the halal label as a mediator. The findings show that product quality, including taste and packaging, as well as social media, through influencer content and reviews on platforms like TikTok and Instagram, are the primary drivers of purchasing decisions. Conversely, the halal label does not directly influence purchases, as Gen Z Muslims consider all instant noodles to be halal certified according to regulations in Indonesia, making it a requirement rather than a differentiating factor. Trust in products, supported by safety certifications such as BPOM, strengthens the perception of halal, but its influence on purchasing is more indirect. This research enriches the Theory of Planned Behavior by demonstrating the dominance of product quality and social media in the context of Muslim Gen Z, while also confirming the halal label as a hygiene factor. Practically, producers are advised to prioritize innovation in product quality and social media campaigns while ensuring transparent halal certification. Limitations of the research include focusing on Muslim Gen Z in Indonesia, so future research may explore other factors such as price or the influence of religious communities.